Zinc borotellurite glass doped with lanthanum nanoparticles, lanthanum and silver oxides as saturable absorber for fiber laser applications - Mohd Fudzi, Faznny (2018)
Improving and enhancing the properties of glasses for the sake of the application of the glass materials in various field are ongoing challenges in materials science and technology. Even though there are research being done on lanthanide elements doped borotellurite glass, but no researchers have tried to incorporate both lanthanum and silver in a glass system to study the changes that both of the element bring about to a glass material. In order to unveil the effect of lanthanum nanoparticles (La NPs), lanthanum oxide (La2O3) and silver oxide (Ag2O) on structural, physical, linear as well as nonlinear optical properties of zinc borotellurite glass system, four series of zinc borotellurite glass doped with various concentration of La2O3, La NPs and Ag2O were prepared by using melt quenching technique. Glass samples in the first and second series were doped with La2O3 and La NPs respectively. The compositions for both first and second glass series were {[(TeO2)0.70(B2O3)0.30]0.70(ZnO)0.30}1-x(La)x where x = 0.00, 0.01, 0.02, 0.03, 0.04 and 0.05 molar fraction. The third and fourth series were fabricated by introducing Ag2O into the best glass sample from the first and second glass series. Thus, the chemical compositions for both the third and fourth series were [{[(TeO2)0.70(B2O3)0.30]0.70(ZnO)0.30}0.96(La)0.04]1-y(Ag2O)y where y = 0.00, 0.02, 0.04, 0.06, 0.08 and 0.10 molar fraction. The structural, physical and linear optical properties of the fabricated glass samples were investigated by using X-Ray Diffraction (XRD) spectrometer, Fourier Transformation Infra-Red (FTIR) spectrometer, Transmission Electron Microscopy (TEM), densimeter and UV-Visible light (UV-Vis) spectrophotometer. The nonlinear optical properties of the glass samples were revealed through Z-scan technique while the ability for the prepared samples to become saturable absorber (SA) was tested in a fiber laser setup. The glassy state and amorphous nature of the prepared glasses had been proven via the presence of a broad hump in the XRD pattern.TeO4, TeO3, BO3 and BO4 structural units were detected in all samples as shown in the FTIR spectra. The existence of La NPs in the second and fourth glass series was verified through TEM with recorded particle size of 30.30 nm and 54.26 nm. The increasing trend of density for all glass samples were obtained because of the incorporation of silver and lanthanum with larger molecular mass in the zinc borotellurite glass system. For glass series without the addition of Ag2O, the indirect optical band gap was found to have increasing trend while the refractive index values decreases in the range of 2.20 to 3.90 eV and 2.19 to 2.50 respectively. On the other hand, the introduction of Ag2O into the zinc borotellurite glass system doped with La2O3 and La NPs had improved the overall optical properties of the glass whereby the optical band gap decreases and refractive index increases drastically within the range of 1.94 to 4.16 eV and 2.14 to 2.76 respectively. Electronic polarizability that is affected by the overall polarizability of the glass system seems to reduce for glass series without the addition of Ag2O while it increases for La2O3, La NPs and Ag2O doped zinc borotellurite glasses. The reason behind the decrement in electronic polarizability is the formation of low polarizability bridging oxygen in La2O3 and La NPs doped zinc borotellurite glass. On the other hand, Ag2O induced the creation of high polarizability nonbridging oxygen that contributes to the increasing electronic polarizability values. Zinc borotellurite glass doped with La2O3, La NPs and Ag2O recorded nonlinear trend on nonlinear refractive index, nonlinear absorption coefficient, third order susceptibility and figure of merit.The fitted open aperture Z-scan plot had recorded both saturable absorber (SA) and reverse saturable absorber (RSA) trends implying the potential of the glass samples to be utilized as SA and nonlinear optical devices. The ability of the glass samples to become SA in erbium doped fiber laser (EDFL) were unveiled for the first time whereby the fabricated samples is able to initiate passively mode-locked and Q-switched pulse laser operation. Dual wavelength mode-locked pulsed laser with high pulse repetition rate of 5 GHz is recorded by utilizing zinc borotellurite glass as SA in the EDFL cavity. In contrast, the utilization of zinc borotellurite glass doped with 0.04 molar fraction of La NPs and 0.10 molar fraction of Ag2O as SA in the same laser cavity, a stable Q-switching laser pulse with high pulse energy of 0.4 μJ is generated. The results from the pulsed laser analysis suggested that zinc borotellurite glass as well as La NPs and Ag2O doped zinc borotellurite glass can be utilized as SA to generate laser pulse with high pulse repetition rate and high pulse energy respectively. This research is able to provide new knowledge on the effect of doping La2O3, La NPs and Ag2O on various properties of zinc borotellurite glass system, the actual relation between result from Z-scan measurement and the ability of a glass material to become SA component as well as unveiling of the ability of glass material to be utilized as SA component in EDFL system.